West meets East toward methodological exchange - Wang, Catherine L.; Ketchen, David J.; Bergh, Donald D. (Research methodology in strategy and management ;, 2012)
This book series' mission is to provide a forum for critique, commentary and discussion about key methodology issues in the strategic management field. Strategic management relies on an array of complex methods drawn from various allied disciplines to examine how managers attempt to lead their firms toward success. The seventh volume of the series is built around the theme of "West Meets East: Toward Methodological Exchange". Within this overarching theme, this volume consists of two parts. The first is "Developing Quantitative Techniques" and the second is "Exploring Mixed Research Methods". With authors from an array of country backgrounds, including Australia, Brazil, Canada, China, Russia, Singapore, the UK and the US, this volume will help promote methodological exchange between the West and the East.